Production of char from coconut dregs / Ku Halim Ku Hamid and Safari Zainal - Ku Hamid, Ku Halim; Zainal, Safari (2002)
Coconut dregs is a waste produced by pressing process of fresh coconut kernel. Large quantity of the dregs produced by fresh coconut milk seller is an advantage to be exploited as a raw material for certain products. In this study. coconut dregs was used to produce char with different time and temperature of carbonization, i.e. 2. 3, and 4 hours and 300. 400. 500 and 600 °C respectively. It was found that temperature and time of carbonization have a significant effect on the yield and quality of char. The proximate analyses was also conducted to determine moisture, ash, volatile matter, and fixed carbon content. Detailed design of the batch operating kiln and its operational procedure are also presented in this paper. The results obtained show that yield of the char produced ranges from 18 to 46 percent from original weight of the dregs. The highest fixed carbon of the char obtained at temperature 600 °C and time 4 hours with 79.43 %, while moisture, volatile matter and ash content are 3.0 8 %,17.11 %, and 0.38 % respectively. The char produced in powder formed exhibit slightly porous structure as shown by BET surface area, iodine number and methylene blue number.